Effect of L-ornithine-L-aspartate Therapy on Low-Grade Hepatic Encephalopathy in Patients with Liver Cirrhosis - Martha Iskandar; Irsan Hasan; Unggul Budihusodo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Minimal hepatic encephalopathy (MHE) is an abnormal condition of psychometric testing before hepatic encephalopathy (HE) condition reducing quality of life and survival rate. Impractical instrument, the psychometric hepatic encephalopathy score (PHES), has been recommended in diagnosing MHE. The new critical flicker frequency (CFF) has good precision and accuracy for diagnosing MHE. Oral L-ornithine-L-aspartate (LOLA) may increase ammonia detoxification. The aim of this study was to recognize the effect of oral LOLA on low-grade HE by investigating the mean value of CFF. Method: We included 31 patients with liver cirrhosis and low-grade HE (MHE, HE grade 1 and 2) at the outpatient clinic of hepatology, Cipto Mangunkusumo hospital between November 2009 and March 2010. It was a double-blind, randomized, placebo-controlled clinical trial. Oral LOLA was administered in a dose of 18 g/day, 3 times daily for 14 consecutive days. At the end of the study, there were 27 cirrhotic patients with CFF value 38 Hz; 14 patients had received LOLA and 13 patients had placebo. Statistic analysis was performed by using the Mann-Whitney U test. Results: The mean value of CFF in LOLA group after treatment (39.3 Hz) was significantly different than the placebo group (36.04 Hz); (p = 0.027). Ammonia level decreased in LOLA group from 118.7 into 109.1 µ mol/L. In placebo group, it increased from 106.9 into 147.5 µ mol/L with p = 0.275 (before); p = 0.052 (after). Conclusion: Oral LOLA may improve the value of CFF and is likely to decrease blood ammonia level in patients with low-grade HE.   Keywords: low-grade hepatic encephalopathy, oral LOLA, CFF improvement, ammonia detoxification